Analisis Pengaruh Kualitas Audit Internal terhadap Efektivitas Kebijakan Lindung Nilai Perusahaan Sektor Energi di Indonesia - Muhammad Abib Nur Alim; Agrianti Komalasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of internal audit quality on the effectiveness of hedging policies in energy sector companies listed on the Indonesia Stock Exchange in 2020-2023. Using annual financial statements and annual reports, this study selected 30 companies using a purposive sampling method. The internal audit variable in this study was measured by three proxies: Internal Audit Charter, Internal Auditor Competence, and Internal Auditor Training. This study used multiple linear regression analysis as a hypothesis testing method. The results indicate that Internal Audit Charter Disclosure has a positive effect on hedging effectiveness disclosure, while Internal Auditor Competence Disclosure and Internal Auditor Training have insignificant and negative effects on hedging policy effectiveness. Based on these results, companies with robust internal audit charters and comprehensive components tend to be more proactive in disclosing hedging policies to avoid reputational or regulatory risks. Companies that disclose internal auditor competency and training through documents do not necessarily guarantee disclosure of hedging effectiveness. This indicates that documentation of internal auditor competency or training in annual reports does not necessarily reflect the overall company oversight.